Promoting health literacy and perceived self-efficacy in people with chronic obstructive pulmonary disease - Fatemeh Aliakbari; Elahe Tavassoli; Forouzan Mohammad Alipour; Morteza Sedehi (Wolters Kluwer Medknow Publications, 2022)
Background: Chronic Obstructive Pulmonary Disease (COPD) is an irreversible condition and it is of great importance for the patients to practice self-care. Given the impact of inadequate health literacy on people's self-efficacy in a self-care program, the aim of this study was to improve health literacy and self-efficacy in people with COPD. Materials and Methods: The present quasi-experimental study was conducted on 70 patients with COPD admitted to Shahrekord educational hospitals in 2019. Using random allocation software, the samples were randomly divided into intervention and control groups. Data collection tools included three questionnaires including demographic, health literacy, and perceived self-efficacy questionnaires. A training program, with three weekly sessions of theoretical and practical trainings, was conducted for the intervention group in classes in the hospital. The time of each session was 40 min. Data were collected three times i.e., before, immediately after, and three months after the trainings. Data were analyzed by means of SPSS 21 statistical software using descriptive and inferential statistics. Results: Before the intervention, the mean scores of perceived self-efficacy and health literacy did not differ significantly between the two groups, but after the intervention, the scores of the members in the intervention group increased significantly (f = 62.15, p < 0.05). Conclusions: The results of the study indicated an increase in the scores of perceived self-efficacy and health literacy in people with COPD. The use of targeted educational interventions can have a positive effect on the treatment and control of the disease.